The dialogue between pedagogy and neuroscience as a new frontier in education - Chiara D'Alessio (Pensa MultiMedia, 2015)
Our work tries to demonstrate how neuroscience is gaining increasing spaces in pedagogy as biology of human mental processes; at the same time pedagogy can help neuroscience to define and clarify the processes that need to be studied to arrive at a deep understanding of biology of the human mind in educational processes. The attempt to achieve common epistemological basis in order to study and refine educational practices, urged by the availability of many neuroscientists to take charge organic layers of complex social behaviors, allows to predict the implications of this combination applied to educational processes, converging pedagogical, psychological, biological studies and correlating their scientific languages from theoretical to applied research. Our work is aimed at creating a new way of thinking in pedagogical sciences, without distinctions between mind and brain, biology and experience, nature and culture: it is is based on the idea that, despite the genetical and constitutional factors play an important role in the development of the human mind, human relations and cultural and social factors implicated in education, through neuroplasticity, can shape the development of the brain and mind and promote a good quality of cognitive, social, emotional functioning. We base our reflections on personalistic anthropology, which connects causality, physiology and phenomenology considering the brain not as a mechanism but as organism with its own teleology, in mutual relationship with the environment, where the human being is a symphony of physical, psychological, social self.